Indian diaspora : socio-cultural and religious worlds - Kumar, P. Pratap, 1952- (International Studies in Religion and Society, 2015)
The chapters presented in this volume represent a wide variety of Indian diasporic experiences. From indenture labour to the present day immigrations, Indian diasporic narrative is one that offers opportunities to evaluate afresh notions of ethnicity, race, caste, gender and religious diversity. From victim discourse to narratives of optimism and complexities of identity issues, the Indian diaspora has exhibited characteristics that enable us as scholars to construct theoretical views on the diaspora and migration. The cases included in this volume will illumine such theoretical ideas. The readers will certainly be able to appreciate the diversity and the depth of these narratives and gain insight into the social and cultural and religious world of the diaspora.